Natural Polymer-Based Antimicrobial Hydrogels without Synthetic Antibiotics as Wound Dressings - Zhong, Yajie; Xiao, Huining; Seidi, Farzad; Jin, Yongcan (Biomacromolecules, 2020)
Wound healing is usually accompanied by bacterial infection. The excessive use of synthetic antibiotics leads to drug resistance, posing a significant threat to human health. Hydrogel-based wound dressings aimed at mitigating bacterial infections have emerged as an effective wound treatment. The review presented herein particularly focuses on the hydrogels originating from natural polymers. To further enhance the performance of wound dressings, various strategies and approaches have been developed to endow the hydrogels with excellent broad-spectrum antibacterial activity. Those that are summarized in the current review are the hydrogels with intrinsic or stimuli-triggered bactericidal properties and others that serve as vehicles for loading antibacterial agents without synthetic antibiotics. Specific attention is paid to antimicrobial mechanisms and the antibacterial performance of hydrogels. Practical antibacterial applications to accelerate the wound healing employing these antibiotic-free hydrogels are also introduced along with the discussion on the current challenges and perspectives leading to new technologies.